A standardized nomenclature and atlas of the female terminalia of Drosophila melanogaster. Issue 1 (31st December 2022) - McQueen, Eden W.; Afkhami, Mehrnaz; Atallah, Joel; Belote, John M.; Gompel, Nicolas; Heifetz, Yael; Kamimura, Yoshitaka; Kornhauser, Shani C.; Masly, John P.; O'Grady, Patrick; Peláez, Julianne; Rebeiz, Mark; et al.
ABSTRACT: The model organism Drosophila melanogaster has become a focal system for investigations of rapidly evolving genital morphology as well as the development and functions of insect reproductive structures. To follow up on a previous paper outlining unifying terminology for the structures of the male terminalia in this species, we offer here a detailed description of the female terminalia of D. melanogaster . Informative diagrams and micrographs are presented to provide a comprehensive overview of the external and internal reproductive structures of females. We propose a collection of terms and definitions to standardize the terminology associated with the female terminalia in D. melanogaster and we provide a correspondence table with the terms previously used. Unifying terminology for both males and females in this species will help to facilitate communication between various disciplines, as well as aid in synthesizing research across publications within a discipline that has historically focused principally on male features. Our efforts to refine and standardize the terminology should expand the utility of this important model system for addressing questions related to the development and evolution of animal genitalia, and morphology in general.